Do bananas chew gum? - Gilson, Jamie (New York : Lothrop, 1980)
Able to read and write at only a second grade level, sixth-grader Sam Mott considers himself dumb until he is prompted to cooperate with those who think something can be done about his problem.
Wilson's Children
School Library Journal
Book Links (A.L.A.)
5.3
3-6
Keywords: Reading disability -- Fiction; Reading disability -- Fiction